THE PRICE OF FAITH IN ALGERIA:1THE NEXUS OF GENDER AND RELIGION BASED ON THE FORBIDDEN WOMEN NOVEL - Mohamad Laudza’i Wafa (Adisam Publisher, 2023)
Sultana Mudjahed had to deal with a series of events that concern her pride as a woman, her faith, her identity, her community, her government and her past. Everything is in the form of a dramatic fiction written by Malika Mokeddem in her work